Method of formalizing the layout of the internal compartments of aircraft - Mikhail Yu. KUPRIKOV; Leonid V. MARKIN (INCAS Bulletin, 2019)
The mathematical formulation of the aircraft’s internal layout problem is described as an optimization problem, with an indication of its objective function, constraints, and performance criteria. The approach (receptor methods and apparatus of normal equations) is justified, which makes it possible to move from enumeration method of placing added objects to intelligent algorithms of automated placement when creating geometric models of automated layout. It was shown that preparing the aircraft for layout automation complicates the mathematical description of geometric models of added objects, increases the complexity of their visualization in modern computer graphics systems and makes the need to create an additional interface between new geometric models and common CAD systems (SolidWorks, AutoCAD, COMPAS, etc.).